(untitled) (Bangladesh Journal of Physics, 2022)
We fabricated the nylon-mesh reinforced epoxy composite by using the hand lay-up method. In this composite, nylon mesh act as the reinforcing material whereas epoxy resin is the matrix material. Comparisons have been made between blank epoxy sheet and the composite. We observed improved mechanical properties such as tensile strength, strain, hardness, and flexural strength from the composited rather than blank epoxy sheet. However, Young’s modulus was not found promising. In case of optical observations, Light absorbance increases, and optical band gap decreases slightly. Considering the Electrical properties, we observed better electrical insulation properties from our fabricated composite than the blank epoxy sheet. In addition, the water absorption properties have also been discussed in this research article. These observations of different properties will contribute to open the new wings of many new applications and help to further improve the quality of the composites. Bangladesh Journal of Physics, 27(2), 49-57, December 2020